The value of money: A survey of heterodox approaches - L. Randall Wray (Levy Economics Institute of Bard College, 2024)
This paper examines heterodox theories of the determinants of the value of money. Orthodox approaches that tie money's value to relative scarcity of money or to the price level are rejected as inconsistent with the monetary theory of production embraced by heterodox traditions linked to Marx, Veblen, and Keynes. This paper examines and integrates (1) recent contributions by David Graeber and Duncan Foley that reinterpret Marx's labor theory of value, (2) the interpretation of Keynes's liquidity preference theory as a theory of asset pricing that began with Sraffa and was further developed by Minsky and Kregel, and (3) Modern Money Theory's approach to sovereign currency. As Heilbroner argued, money is central to the internal logic of the capitalist system, and is what makes capitalism truly different from other social organizations. Our theory of value informs our beliefs about how the deep structure of the economic system generates a system of prices denominated in the money of account.
Keywords: B14; 24; 25; B51; 52; E11; 12; B62; 330; Labor theory of value; Modern Money Theory; Liquidity Preference; Monetary Theory of Production; Marx; Keynes; Minsky; Graeber; Foley; Sraffa; Heilbroner